Heavy Metal Distribution In Suspended Load And Bed Load At The Perai River - Karib, Muhammad Izzuddin Mohd (Universiti Sains Malaysia, 2022)
Penang is currently having a problem with the water authority due to the transboundary of the Muda River between two inter-states Kedah and Penang. Therefore, the Perai River is an alternative water resource to Penang and a backup plan for a new water intake. The objective of this study to identify the heavy metals in suspended load and bed load and establish the correlation between heavy metals in the suspended load, bulk sample, and bed loads. Four significant metals, namely iron, mercury, aluminum, and zinc were obtained from the suspended load, bulk sample, and bed loads at eleven sampling points within the catchment. Sampling campaigns were conducted in February and April within the basin. The river water and bed load sample were processed and analyzed for heavy metals; Al, Hg, Zn, and Fe, using ICP-OES. The heavy metals found in the river were in range: for total recoverable Hg (0.1175-0.4202 mg/L); Al (6.4358-103.0910 mg/L); Fe (1.5837-41.2027 mg/L); Zn (0.0618-0.3315 mg/L), for suspended loads Hg (0.0131-0.2149 mg/L); Al (2.0788-44.6050 mg/L); Fe (1.0110-27.6687 mg/L); Zn (0.5514-7.5588 mg/L), and for bed loads Hg (0.0115-0.1577 mg/L); Al (531.7650-6710.72 mg/L); Fe (165.1470-2056.1300 mg/L); Zn (1.3631-13.6802) of concentration heavy metal respectively. The correlation between the concentration of heavy metals in total recoverable suspended loads, and bed load hold for all sampling points has very good linear correlations. The results achieved by these linear regressions were in very good agreement with independently measured values for the concentration of heavy metals in total recoverable, suspended loads, and bed load taken at the same sampling points. Based on the National Water Quality Standard (NWQS) and Ministry of Health (MOH) guidelines, these four heavy metals exceeded the maximum permissible limit and as far and is very highly polluted in the Perai River.